Transcriptional control of physiological and pathological processes by the nuclear receptor PPARβ/δ - Tan, Nguan Soon (2017)
Peroxisome proliferator-activated receptors (PPARs) are a class of transcription factors that belong to the nuclear hormone receptor superfamily, and their activities are dependent on their respective ligands. Since the discovery of PPARα (NR1C1) as a receptor that mediates peroxisome proliferation in rodent hepatocytes in 1990 [1], two other isotypes, PPARβ/δ (NR1C2) and PPARγ (NR1C3), were subsequently identified and characterized [2,3]. Members of the PPAR family have been extensively linked to numerous systemic and cellular activities that range far beyond simply mediating peroxisome proliferation in rodents [4]. Dependent on isotype-specific or shared tissue expression, all three PPARs regulate different or, in some cases, overlapping functions [5]. PPARα and PPARγ have established roles in fatty acid (FA) catabolism and in adipocyte differentiation and lipid storage, respectively, and both are pharmacological targets of FDA-approved drugs for the treatment of numerous metabolic diseases [6,7]. In contrast, no PPARβ/δ ligands are currently used in the treatment of any disease, although small studies on human subjects have used PPARβ/δ ligands to treat metabolic syndrome [8,9]. PPARβ/δ is expressed in numerous tissues [10,11], and many important functions have been attributed to PPARβ/δ in skeletal muscle, adipose tissue, the cardiovascular system, uterine implantation, the gut, the brain, and skin [12]. These factors make PPARβ/δ a very attractive and challenging target, as it is involved in numerous key functions, such as energy metabolism, cellular differentiation and proliferation, tissue repair, and cancer progression.